YouTube as digital public sphere: Controversary over Indonesia’s Military Reform Law - Putri, Lutfiani Sayyida Eka; Lestari, Kalimah Wasis; Payo, Nadia; Ambardo, Marsha; Nareshwari, Syalsabila Amalia; Aqila, Ratu Sakinatul; Cahyani, Eylin Intan Regita; Sahara, Berliana Elsa (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2025)
The issue of revising the TNI Law has been considered an offense against the principles of democracy and civil supremacy, triggering fears of the military's dual function (including involvement in socio-political affairs), as seen during Suharto's New Order era. This research aims to analyze the pros and cons of the audience of the Bocor Alus Politik YouTube channel towards the Revision of the Indonesian National Army Law (RUU TNI) through the comments of the content titled "Actors & Lobbies behind the Revision of the TNI Law". This research employs a quantitative approach, utilizing a sentiment analysis method to classify netizen comments. The research data consisted of 4,209 comments collected from the YouTube content. The analysis results indicate dominance of positive sentiment (3,694 comments) over negative sentiment (512 comments), with an accuracy rate of 86.20%. The positive group used appreciative words such as "support", "brave", and "media", which showed support for civil supremacy and independent media. Meanwhile, the negative group employs diction that delegitimizes the media, using words such as "stooge" and "slander", reflecting skepticism towards media objectivity and support for military involvement in the civilian sector. This research demonstrates that YouTube serves as a digital deliberation arena, showing the political polarization of Indonesian society regarding civil-military relations.